N2O source partitioning in soils using 15N site preference values corrected for the N2O reduction effect. (1st February 2016) - Wu, Di; Köster, Jan Reent; Cárdenas, Laura M.; Brüggemann, Nicolas; Lewicka‐Szczebak, Dominika; Bol, Roland
Abstract : Rationale: The aim of this study was to determine the impact of isotope fractionation associated with N2 O reduction during soil denitrification on N2 O site preference (SP) values and hence quantify the potential bias on SP‐based N2 O source partitioning. Methods: The N2 O SP values ( n  = 431) were derived from six soil incubation studies in N2 ‐free atmosphere, and determined by isotope ratio mass spectrometry (IRMS). The N2 and N2 O concentrations were measured directly by gas chromatography. Net isotope effects (NIE) during N2 O reduction to N2 were compensated for using three different approaches: a closed‐system model, an open‐system model and a dynamic apparent NIE function. The resulting SP values were used for N2 O source partitioning based on a two end‐member isotopic mass balance. Results: The average SP0 value, i.e. the average SP values of N2 O prior to N2 O reduction, was recalculated with the closed‐system model, resulting in −2.6 ‰ (±9.5), while the open‐system model and the dynamic apparent NIE model gave average SP0 values of 2.9 ‰ (±6.3) and 1.7 ‰ (±6.3), respectively. The average source contribution of N2 O from nitrification/fungal denitrification was 18.7% (±21.0) according to the closed‐system model, while the open‐system model and the dynamic apparent NIE function resulted in values of 31.0% (±14.0) and 28.3% (±14.0), respectively. Conclusions: Using a closed‐system model with a fixed SP isotope effect may significantly overestimate the N2 O reduction effect on SP values, especially when N2 O reduction rates are high. This is probably due to soil inhomogeneity and can be compensated for by the application of a dynamic apparent NIE function, which takes the variable reduction rates in soil micropores into account. Copyright © 2016 John Wiley & Sons, Ltd.